2017
DOI: 10.1007/s13365-017-0553-9
|View full text |Cite
|
Sign up to set email alerts
|

Combination antiretroviral therapy improves cognitive performance and functional connectivity in treatment-naïve HIV-infected individuals

Abstract: Our study aimed to investigate the short-term effect of combination antiretroviral therapy (cART) on cognitive performance and functional and structural connectivity and their relationship to plasma levels of antiretroviral (ARV) drugs. Seventeen ARV treatment-naïve HIV-infected individuals (baseline mean CD4 cell count, 479 ± 48 cells/mm3) were age matched with 17 HIV-uninfected individuals. All subjects underwent a detailed neurocognitive and functional assessment and magnetic resonance imaging. HIV-infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
55
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 45 publications
7
55
2
Order By: Relevance
“…However, previous studies observed improved functional connectivity in HIV patients that received medications ( Ortega et al, 2015 ). Another study showed that cART improves cognitive performance and functional connectivity in ARV treated-naïve HIV-infected individuals ( Zhuang et al, 2017 ). We are expecting similar impact of cART treatment on patients included in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies observed improved functional connectivity in HIV patients that received medications ( Ortega et al, 2015 ). Another study showed that cART improves cognitive performance and functional connectivity in ARV treated-naïve HIV-infected individuals ( Zhuang et al, 2017 ). We are expecting similar impact of cART treatment on patients included in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In Malawi, in spite of a generalized HIV epidemic and a mature HIV response, approximately 250,000 HIV‐positive adults remain unaware that they are living with HIV . This makes them unable to access antiretroviral therapy (ART) which has proven benefits for the health of the individual and prevention of horizontal and vertical transmission .…”
Section: Introductionmentioning
confidence: 99%
“…In both studies, the neuropsychological tests were assessed by AIDS Dementia Complex (ADC) staging according to the Memorial Sloan Kettering (MSK) staging system, and an ADC score of 0 or 0.5 was considered neurocognitive asymptomatic. Zhuang Y et al investigated WM changes in ANI patients diagnosed according to the Frascati criteria [ 3 ] and found no significant WM microstructural differences between HIV-infected and healthy controls [ 18 ]. Cysique LA et al reported that the location of WM injury in ANI cases was the anterior limb of the internal capsule [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary oligodendrocyte and myelin damage leading to secondary axonal damage (outside-in) or primary axonopathy triggering oligodendrocyte injury and demyelination (inside-out) are indistinguishable [ 20 ]. WM alterations may contribute to cognitive deficits in HIV-infected patients [ 7 , 18 , 21 ]. It is worth noting that the relationship between WM abnormalities and cognitive status has not been well characterized or systematically assessed.…”
Section: Introductionmentioning
confidence: 99%